Methods of Expressing Incentives in Uzbek Language - Mukhamadkhonovna, Buzrukova Makhina (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the features of incentive structures in the Uzbek literary text. It also provides specific examples of prescriptive, requestive and suggestive incentive structures and their analysis in the work of the Uzbek writer Abdullah Kadiri, “Past Days”.